Map of 16 polymorphic loci on the short arm of chromosome 16 close to the polycystic kidney disease gene (PKD1). Issue 10 (October 1990) - Breuning, M H; Snijdewint, F G; Brunner, H; Verwest, A; Ijdo, J W; Saris, J J; Dauwerse, J G; Blonden, L; Keith, T; Callen, D F
Abstract : To define the PKD1 locus further, the gene involved in the most frequent form of adult polycystic kidney disease, probes from 16 polymorphic loci were mapped on 16p13.1-pter with the combined use of cell lines containing rearranged chromosomes and family studies. Five breakpoints in the distal part of 16p arbitrarily subdivided the loci into five groups. By analysing 58 recombination events among 259 informative meioses in 12 large families with PKD, we were able to construct a linkage map for the distal part of 16p. The order of the markers obtained with chromosomal rearrangements was confirmed by the family studies. The D16S85 locus near alpha globin, D16S21, and D16S83 map distal, or telomeric, to PKD1. The polymorphic red cell enzyme phosphoglycolate phosphatase (PGP), D16S84, D16S259, and D16S246 showed no recombination with PKD1. The remaining nine RFLPs all map proximal to the PKD1 gene. By cosmid walking, additional RFLPs were detected at the D16S21 locus. A single intrahaplotype recombination observed defines the orientation of D16S21 relative to PKD1. The new polymorphisms are valuable for presymptomatic and prenatal diagnosis of PKD1. Furthermore, our map is both a good starting point for the physical map of 16p and a useful tool for the isolation of the PKD1 gene.